2007
DOI: 10.1111/j.1365-2907.2007.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Spleen mass as a measure of immune strength in mammals

Abstract: 1. In studies of birds and their pathogens, spleen size has frequently been used to make inferences about immune system strength. However, the use of spleen size in mammals is more complicated because, in addition to having an immune function, the mammalian spleen is also a reservoir for red blood cells. 2.To assess the reliability of mammalian spleen mass as an indicator of immune activity, we quantified the white and red pulp mass by histology of spleens from shot red deer Cervus elaphus. We then analysed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 21 publications
1
47
2
Order By: Relevance
“…Generally, increased spleen and liver masses are associated with a classic inflammatory response (Hart, 1988). Many studies have demonstrated that spleen mass is commonly negatively associated with overall body condition and positively correlated with parasite infection (Corbin et al, 2008;Cowan et al, 2009;Schulte-Hostedde and Elsasser, 2011). As seen previously (Swallow et al, 2005;Meek et al, 2009;Downs et al, 2012), spleen and liver masses were not significantly different between HR and C mice, and mini-muscle mice had heavier livers.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Generally, increased spleen and liver masses are associated with a classic inflammatory response (Hart, 1988). Many studies have demonstrated that spleen mass is commonly negatively associated with overall body condition and positively correlated with parasite infection (Corbin et al, 2008;Cowan et al, 2009;Schulte-Hostedde and Elsasser, 2011). As seen previously (Swallow et al, 2005;Meek et al, 2009;Downs et al, 2012), spleen and liver masses were not significantly different between HR and C mice, and mini-muscle mice had heavier livers.…”
Section: Discussionsupporting
confidence: 49%
“…However, the spleen is often enlarged in organisms with parasitic infections, perhaps indicating heightened immune response caused by increased production/storage of lymphocytes and immunoglobulins. As the spleen is considered to be an immunologically important organ (Corbin et al, 2008;Cowan et al, 2009;Schulte-Hostedde and Elsasser, 2011), spleen mass is expected to increase with infection. Additionally, hematocrit is expected to be positively correlated with both infection (Meagher, 1998;Downs et al, 2012) and V · O2max performance.…”
Section: Introductionmentioning
confidence: 99%
“…This was explained as an investment in the production and stockage of lymphocytes in the spleen in order to counteract potential infections (Møller et al, 1998). However, other studies have suggested that spleen mass reflects the host condition and therefore should be negatively related to parasite infection (Corbin et al, 2008;Lutermann and Bennett, 2008;Navarro-Gonzalez et al, 2011). However, these hypotheses are not mutually exclusive.…”
Section: Impacts Of Parasites and Parasite Risk On Spleen Size And Inmentioning
confidence: 82%
“…(ii) Evaluation of immunocompetence We used spleen mass as our measure of immunocompetence as (i) spleen tissue is involved both in humoral and cellular immune responses, (ii) it has previously been shown to correlate negatively with nematode parasite burden in the red deer ( Vicente et al 2007;Corbin et al 2008).…”
Section: Ectoparasitesmentioning
confidence: 99%